2020
DOI: 10.15421/022017
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis, pigment content, phytohormones and productivity of eggplants under the action of gibberellin and tebuconazole

Abstract: Regulation of growth and development of cultivated plants in order to optimize the production process is one of the main objectives of modern plant physiology. Both activators and growth inhibitors are used for this purpose. The effect of foliar treatment with 0.005% solution of gibberellic acid and 0.025% solution of antigibberellic preparation of tebuconazole on the morphogenesis, leaf structure, photosynthetic pigment content, balance of phytohormones and eggplant productivity cv. Diamond variety was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…We showed that under the action of EW-250 the content of GA3 and IAA in the stems and leaves of pepper decreased, and the content of ABA in the leaves increased against the background of inhibited stem growth and increased mass of crude matter of all vegetative organs. The obtained data complement our results of anatomical-morphological and physiological-biochemical studies of eggplant plants (Rogach et al, 2020) as well as the work of other authors on the effects of triazolederived retardants of paclobutrazole shown for magnolia plants (Shi et al, 2021), uniconazole -for winter barley plants (Bakheta & Hussein, 2014) and hexaconazole -for cucumber plants (Tae-Yun & Jung-Hee, 2012).…”
Section: Tablesupporting
confidence: 88%
See 4 more Smart Citations
“…We showed that under the action of EW-250 the content of GA3 and IAA in the stems and leaves of pepper decreased, and the content of ABA in the leaves increased against the background of inhibited stem growth and increased mass of crude matter of all vegetative organs. The obtained data complement our results of anatomical-morphological and physiological-biochemical studies of eggplant plants (Rogach et al, 2020) as well as the work of other authors on the effects of triazolederived retardants of paclobutrazole shown for magnolia plants (Shi et al, 2021), uniconazole -for winter barley plants (Bakheta & Hussein, 2014) and hexaconazole -for cucumber plants (Tae-Yun & Jung-Hee, 2012).…”
Section: Tablesupporting
confidence: 88%
“…It is found that the use of exogenous GA3 and anti-gibberellin triazole derivative EW-250 led to crucial changes in the growth rate of pepper plants. In our previous study on eggplant culture, similar results were obtained (Rogach et al, 2020). The increase in the linear size of the shoots of GA3-treated plants and the raw biomass of roots, stems and leaves correlated with the increase in the content of endogenous GA3 in the stems and GA3 and IAA in the leaves.…”
Section: Tablesupporting
confidence: 82%
See 3 more Smart Citations